Chondrogenic differentiation induced by extracellular vesicles bound to a nanofibrous substrate - Casanova, MR (2021)
Extracellular vesicles (EVs) are being increasingly studied owing to its regenerative potential, namely EVs derived from human bone marrow mesenchymal stem cells (hBM-MSCs). Those can be used for controlling inflammation, repairing injury, and enhancing tissue regeneration. Differently, the potential of EVs derived from human articular chondrocytes (hACs) to promote cartilage regeneration has not been thoroughly investigated. This work aims to develop an EVs immobilization system capable of selectively bind EVs present in conditioned medium obtained from cultures of hACs or hBM-MSC. For that, an anti-CD63 antibody was immobilized at the surface of an activated and functionalized electrospun nanofibrous mesh. The chondrogenic potential of bound EVs was further assessed by culturing hBM-MSCs during 28 days under basal conditions. EVs derived from hACs cultured under differentiation medium or from chondrogenically committed hBM-MSCs induced a chondrogenic phenotype characterized by marked induction of SOX9, COMP, Aggrecan and Collagen type II, and matrix glycosaminoglycans synthesis. Indeed, both EVs immobilization systems outperformed the currently used chondroinductive strategies. These data show that naturally secreted EVs can guide the chondrogenic commitment of hBM-MSCs in the absence of any other chemical or genetic chondrogenic inductors based in medium supplementation.